Increased astrocyte representation in the hippocampus of 5xFAD mice - Jovanović, Violeta; Despotovic, Jelica; Balo, Mario; Zaletel, Ivan; Despotovic, Sanja; Puskas, Nela (Medicinski podmladak, 2021)
Introduction: Alzheimer's disease is the most common neurodegenerative disorder, characterized by the formation of amyloid plaques and the neurofibrillary tangles in the brain of a sick person, leading to neuronal damage and loss. Activation of astrocytes and astrogliosis occurs along with this process. Due to ethical limitations in working with human tissue, numerous transgenic animal models have been developed to study the pathogenesis of this processes. Early Aβ deposition is observed in the cortex and the hippocampus.Aim: The aim of this study was to determine the difference in the presence of GFAP positive cells in the hippocampus between transgenic 5xFAD mice aged 36 weeks and their corresponding controls.Material and methods: The 5xFAD mice model of Alzheimer's disease was used, characterized by early formation of amyloid plaques but without the presence of a neurofibrillar tangles. Transgenic and control animals were sacrificed at 36 weeks of age. The visualization of GFAP-positive cells in the hippocampus of their brains was done by using immunohistochemistry and antibodie for glial fibrillary acidic protein – GFAP, the major marker of astrocytes. Quantification of immunoreactivity was done by using Icy software system.Results: There was a statistically significant difference in the expression of GFAP in the dentate gyrus and the granular zone of the hippocampus between the transgenic and control group at 36 weeks of age, while significant change in the CA1-3 regions was not observed between investigated groups.Conclusion: Obtained results confirm involvement of astrogliosis in the pathophysiology of Alzheimer's disease, but also indicate an earlier occurrence of astrogliosis in the dentate gyrus and granular zone in relation to other regions of the hippocampus in the 36-week-old 5xFAD mice.
Keywords: Alzheimer's disease; 5xFAD; hippocampus; astrocytes; GFAP